Land Suitability for Ciplukan (Physalisangulata L.)Using Multicriteria Analysis - Nur Adliani; Nirmawana Simarmata; . Heriasnyah (Journal of Science and Applicative Technology, 2019)
The study investigated the suitable land of Ciplukan (Physalisangulata L.), which is a source of medicine ingredient to lower the level of blood sugar. Ciplukan generally grows among wild plants. The objective of this research is to describe the characteristics of the land to grow ciplukan based on the land suitability. The class of land suitability is obtained by matching the physical character and chemistry from botanical garden land and overlaying appropriate maps with the requirements of growing ciplukan with ArcGIS. The class of suitability land acquired in the Botanical Gardens that earned the score of 6 to 8 is an area that does not suitable to cultivate the plants ,with the size 52,189Ha. The score of the lesser appropriate classification was of 9 to 11 with the size of area 180,966Ha. The score of 12 has the size of area 49,111Ha. The score of 12 fulfills 4 parameters. If all the land were suitable, then it would worth 3.9 to 11. The parameters which were not corresponding at all is the value of score was 6 to8. The actual area at the Botanical Garden land was 80 Ha. So, some parts of the land can be used to grow ciplukan.